Tag questions - David Brazil (Ilha do Desterro)
The so-called 'tag' structures of English have received a lot of attention in language teaching programmes, attention that is not hard to justify when one considers the problems and anxiety they can occasion for many foreign learners. Most teachers one speaks to seem fairly willing to agree, however, that traditional treatments of the topic leave much to be desired. It happens, also, that, when considered collectively, the tags and some related phenomena have a special heoretical interest. For they constitute a field in which it seems essential to bring together insights that derive from the study of several aspects of linguistic organisation, aspects which in some recent work have been held to need distinctive kinds of descriptive category to handle. Traditional treatments have found it necessary to recognise different syntactic types (e.g. 'same polarity' and 'reversed polarity' tags) and ifferent intonational treatments ("falling'and 'rising' tag); while the way the communicative significance of the various permutations is described normally requires reference to the expectations they signal regarding the immediately following behaviour of the other party (in the common phrase, 'What kind of answer they expect'). This last consideration places the matter squarely in the arena of recent work on the analysis of interactive discourse.